Sugaring time - Lasky, Kathryn; Knight, Christopher G. (New York Macmillan Publishing Company, 1986)
Text and photographs show how a family taps the sap from maple trees and processes it into maple syrup.
First Aladdin Books edition 1986.
Keywords: Sugar maple -- Tapping -- Juvenile literature; Maple syrup -- Juvenile literature; Maple syrup; Maple sugar